Cottone's practical infection control in dentistry - Molinari, John A.; Harte, Jennifer A. (Lippincott William & Wilkins, 2010)
Now in its Third Edition, this book is a primary, comprehensive infection control text for students in the dental professions. Using the latest scientific and clinical evidence and current infection control guidelines, the book presents easy-to-follow protocols as components of a basic infection control routine. This Third Edition has been thoroughly updated and contains more photographs and tables. A glossary of terminology and acronyms appears at the beginning of each chapter
Rev. ed. of: Practical infection control in dentistry / James A. Cottone. 2nd ed. 1996
Keywords: Asepsis and antisepsis; Cross infection -- Prevention; Dental offices -- Sanitation; Dentistry